(untitled) (Gilgameš, 2016)
In the collections of the Real Armería of Madrid it is conserved a shield known as Plus Ultra or Apotheosis of Charles V. The young emperor Charles V is compared, until 1516, to the mythical hero Hercules, who placed two columns at the edge of the known world. Starting from 1530 this identification is accompanied with a new image of the emperor. The shield shows a new iconography inspired by that of a Roman ruler, based on knowledge of classical culture. The Emperor is portrayed with different symbols of his power, reminiscent of the military victory of Tunis.